PENGEMBANGAN PAKET EKOWISATA DI BALE MANGROVE LOMBOK TIMUR - Yuliana Pebrianti,; Jumraidin, Jumraidin; H. Lalu Ratmaja, (Juremi: Jurnal Riset Ekonomi, 2024)
This research aims to illustrate the development of ecotourism packages in Bale Mangrove, East Lombok. This research is classified as descriptive qualitative research using data collection techniques such as observations, interviews, and documentation. The data analysis techniques used in this study are qualitative data analysis, which includes data reduction, data presentation, and inference drawing. The conclusion is taken from the source, namely the Bale Mangrove tourism manager. The results of this research show that the provision of adequate facilities and infrastructure, the potential of various tourist attractions, detailed pricing of tourist attractions, and the clear target market support the development of mangrove ecotourism packages in Bale Mangrove through stages in accordance with the theory used by the researchers. Bale Mangrove is located in Poton Bako Hamlet, Jerowaru Village, East Lombok, and has various potential tourist attractions, stages of tourism package development, target market, and mangrove ecotourism package development for the use of managers.